Parents, peers, and low self-control: Exploring the impact of time varying factors associated with deviance in early- and middle-adolescence. (January 2023) - Bryson, Sara L.; Baker, Thomas; Ray, James V.; Metcalfe, Christi
Abstract: Prior research finds an association between parental attachment, peer delinquency, low self-control, and deviant behavior among adolescents. However, longitudinal research related to these associations typically examines only one specific developmental period or explores multiple waves without considering changes across developmental periods. The failure to account for shifting periods in development can lead to conclusions regarding the correlates of deviance that ignore their age-graded impact. This study demonstrates how exploring all six-waves of data from a longitudinal study of Korean adolescents leads to conclusions regarding parents, peers, and low self-control that may misrepresent their influence. Alternatively, when the data is examined based on stages of adolescence—divided into early and middle adolescence—a clearer picture of the age-graded influence of parents, peers, and low self-control emerges. Specifically, when analyzed as a whole, parental attachment appears to have an enduring significant association with deviance. When analyzed by stage of adolescence, it becomes clear that parental attachment is significantly associated with deviance only in early-adolescence, and in middle-adolescence, peer delinquency emerges as most relevant. Importantly, low self-control is consistently associated with delinquency across all stages.